Synthesis of sulfonium N-chloramines for antibacterial applications. (6th December 2019) - Li, Lingdong; Jia, Dongxue; Wang, Hande; Chang, Chang; Yan, Jiawei; Zhao, Zongbao Kent
Abstract : Sulfonium N -chloramines were synthesized with significantly higher antibacterial efficacy than previous quaternary ammonium counterpart 1, and the highest efficacy was achieved for dodecyl chained N -chloramine 9 due to a synergistic biocidal effect. Abstract : For the first time sulfonium N -chloramines were chemically synthesized, which displayed significantly higher biocidal efficacy than the previously reported quaternary ammonium counterpart. Noticeable synergistic biocidal efficacy was observed between the dodecyl chain tethered sulfonium centre and the N -chloramine moiety, exerting the highest antibacterial efficacy so far of all cationic N -chloramines.